Dapagliflozin in patients with type 2 diabetes receiving high doses of insulin: efficacy and safety over 2 years. Issue 2 (29th August 2013) - Wilding, J. P. H.; Woo, V.; Rohwedder, K.; Sugg, J.; Parikh, S.; ,
Abstract Aims Dapagliflozin, a selective inhibitor of sodium‐glucose cotransporter 2 (SGLT2), has been shown to improve glycaemic control, stabilize insulin dosing and mitigate insulin‐associated weight gain over 48 weeks in patients whose type 2 diabetes mellitus (T2DM) was inadequately controlled despite high doses of insulin. Here the efficacy and safety of dapagliflozin therapy after a total of 104 weeks are evaluated in this population. Methods This was a 24‐week, randomized, placebo‐controlled, double‐blinded, multicentre trial followed by two site‐ and patient‐blinded extension periods of 24 and 56 weeks (NCT00673231), respectively. A total of 808 patients, whose T2DM was inadequately controlled on insulin ≥30 IU/day, with or without up to two oral antidiabetic drugs, were randomly assigned to receive placebo or 2.5, 5 or 10 mg/day of dapagliflozin for 104 weeks. At 48 weeks, patients on dapagliflozin 5 mg were switched to 10 mg. Outcomes over 104 weeks included change from baseline in HbA1c, insulin dose and body weight; analyses used observed cases and included data after insulin up‐titration. Adverse events (AEs) were evaluated throughout 104 weeks. Results Five hundred and thirteen patients (63.6%) completed the study. Mean HbA1c changes from baseline at 104 weeks were −0.4% in the placebo group and −0.6 to −0.8% in the dapagliflozin groups. In the placebo group, mean insulin dose increased by 18.3 IU/day and weight increased by 1.8 kg at 104 weeks, whereas in the dapagliflozin groups, insulin dose was stable and weight decreased by 0.9–1.4 kg. AEs, including hypoglycaemia, were balanced across groups. Proportions of patients with events suggestive of genital infection and of urinary tract infection (UTI) were higher with dapagliflozin versus placebo (genital infection 7.4–14.3% vs. 3.0%; UTI 8.4–13.8% vs. 5.6%) but most occurred in the first 24 weeks and most were single episodes that responded to routine management. Conclusions Dapagliflozin improved glycaemic control, stabilized insulin dosing and reduced weight without increasing major hypoglycaemic episodes over 104 weeks in patients whose T2DM was inadequately controlled on insulin. However, rates of genital infection and of UTI were elevated with dapagliflozin therapy.